0053 SUVN-G3031: Safety, Tolerability and Pharmacokinetics of a Potent and Selective Histamine H3 Receptor Inverse Agonist - Single and Multiple Ascending Doses in Healthy Subjects. (12th April 2019) - Nirogi, Ramakrishna; Shinde, Anil; Mudigonda, Koteshwara; Bhyrapuneni, Gopinadh; Muddana, Nageswara Rao; Palacharla, Raghava Chowdary; Ajjala, Devender Reddy; Goyal, Vinod Kumar; Ravula, Jyothsna; Jetta, Satish; Mohammed, Abdul Rasheed
Abstract: Introduction: SUVN-G3031, potent and selective H3 receptor inverse agonist is being developed for the treatment of sleep related disorders. SUVN-G3031 modulates neurotransmitters involved in the maintenance of wakefulness and treatment of cataplexy. EEG in rodents produced wake promoting effects. Preclinical results provide a strong support for the potential therapeutic utility of SUVN-G3031 in sleep related disorders. Methods: SUVN-G3031 was studied in a single-center, multifaceted phase 1 clinical studies (US IND) to evaluate its safety, tolerability, and pharmacokinetics after single and multiple ascending doses in healthy subjects. For single ascending dose evaluation, healthy subjects were dosed with 0.1, 1, 6, 12, and 20 mg of SUVN-G3031. In multiple dose evaluation, once daily dose of 1, 3, and 6 mg were administered for 14 days in healthy adult male subjects. Effect of food, gender and age on pharmacokinetics was evaluated in healthy subjects at the dose of 6 mg. SUVN-G3031 was quantified in plasma using a validated LC-MS/MS method. Safety and tolerability was evaluated based on assessments of adverse events, physical examinations, laboratory tests, vital signs, 12-lead ECGs and continuous telemetry. Results: Absorption of SUVN-G3031 was rapid and exposures were dose proportional at tested doses between 0.1 to 20 mg. SUVN-G3031 achieved the projected efficacy concentrations and attained steady state on day five in tested population on multiple administration. Food, gender and age had no effect on the pharmacokinetics of SUVN-G3031. SUVN-G3031 was well tolerated up to the highest tested dose of 20 mg/day single dose or 6 mg repeated dose in healthy subjects. Conclusion: SUVN-G3031 has favorable safety and pharmacokinetic profile in healthy subjects. SUVN-G3031 is well tolerated in humans with adequate plasma exposure for efficacy and favorable pharmacokinetics suitable for once a day oral administration. Phase 2 POC study for the treatment of narcolepsy is being planned in USA. Support (If Any): None